Xstyle.Id Marketing Communication Mix Implementation In Introducing Thrift Shop’s Product - Adevy Vanie; Eka Megawati; Azhar Maulana Yunior (International Journal of Education, Information Technology, and Others, 2023)
The emerging fast-fashion market has impact on some environmental issues due to unsustainable consumption. Thrift shop became a business opportunity that could reduce these issues in fast-fashion industry by selling second-hand or preloved products to the targeted consumers. Thrift shop already existed since long time ago but the trend became more popular among young generation as they more concerned about environmental issues. Influence of public figures or celebrities in social media platforms also contributed to the thrift shop hype especially among the millennials who idolized them. As more thrift shops entered fast-fashion industry, marketing communication mix became competitive strategy for introducing the products and building public awareness. XStyle.id was one of thrift shops that adopted variety tools as its marketing communication mix to introduce the thrift products to both potential and existing customers. By implementing different tools such as advertising, sales promotion, public relations, personal selling as well as direct marketing, XStyle.id able to reach and inform the customers about thrifting which many people might not use to buy second-hand products. The research aims to understand how XStyle.id use marketing communication mix in introducing the thrift shop’s product to the public. The research used qualitative descriptive method by collecting data through in-depth-interviews, observations, and literature reviews. The findings showed that there are five tools of marketing communication that being used both online and offline based to introduce thrift shop’s product